2017
DOI: 10.1017/s1744133116000426
|View full text |Cite
|
Sign up to set email alerts
|

Raising more domestic money for health: prospects for low- and middle-income countries

Abstract: Since the 2007/2008 financial crisis, the rhetoric in the development assistance dialogue has shifted away from raising more international funding for health, to requesting countries to move toward self-sufficiency. This paper examines the potential of 46 countries identified by an international panel in 2009 as being of high need to raise additional funding for health from domestic sources. Economic growth alone would allow 12 of them to reach a level of health spending where their populations could have acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…The 2030 Agenda for Sustainable Development also underscores that each country has primary responsibility for its own economic and social development. One of the targets highlighted in the Towards a coherent global framework 291 Agenda is to strengthen domestic resource mobilisation, and the scope for doing this is thoroughly examined in this special issue (Elovainio & Evans, 2017;Meheus and McIntyre, 2017). Concurrently, there has been a number of calls for better use of resources.…”
Section: Domestic Financing Of Health Systemsmentioning
confidence: 99%
“…The 2030 Agenda for Sustainable Development also underscores that each country has primary responsibility for its own economic and social development. One of the targets highlighted in the Towards a coherent global framework 291 Agenda is to strengthen domestic resource mobilisation, and the scope for doing this is thoroughly examined in this special issue (Elovainio & Evans, 2017;Meheus and McIntyre, 2017). Concurrently, there has been a number of calls for better use of resources.…”
Section: Domestic Financing Of Health Systemsmentioning
confidence: 99%
“…There is growing recognition that low- and middle-income countries must find additional public domestic sources of finance if they want to make tangible and sustained progress towards UHC, given the relatively low levels of public funding for health care in many of these countries at present and the challenges arising from a heavy dependence on donor funding [3–5]. Thus, there is an increased focus on how to create fiscal space for health, which ‘refers to the capacity of government to provide additional resources for health without jeopardising its long-term financial position and economic stability’ [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing literature exploring ways in which government revenue could be increased, ranging from improving tax revenue collection and administration efficiency, to increasing rates of existing taxes and introducing new taxes or other government revenue sources, such as from the extraction of natural resources [3,10–20]. Some studies model the additional government revenue that could be generated through such strategies, and the potential increases in government health expenditure [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Using available capacities through peers support and supporting burn patients to improve their health status also have been emphasized by WHO in developed countries[5]. Evidences shows that intra-sectoral collaboration mechanisms such as redistribution of state's available resources and/or reducing subsidies of some goods and allocating released resources to health, efficiency of tax system, expansion of formal sector, using opportunities of levering tax rate on, harmful services and behaviours, applying custom tariffs and earmarked taxes on stakeholders that influence incidence of burn injuries and accidents as well as voluntary income sources from private sector, can provide new resources to cover rising healthcare expenditures[47].The results also revealed that incomplete benefit package for burn patients, insufficient health insurance coverage (particularly for foreigners), and inappropriate coverage of health expenditures by basic health insurance schemes, are the most important challenges related to sub-function of resource pooling in burn care in Iran. A study on reimbursing hospital bills in a profit SBH in the USA found a significant difference between bills and the amount that was reimbursed to the hospital by Medicaid.…”
mentioning
confidence: 99%